Adaptación de la "Escala de Autocrítica Rumiativa" de Smart, Peters y Baer en estudiantes universitarios de Lima Metropolitana - Macher Barcenas, Jorge Andrés (2020)
The goal of the present investigation consisted in the adaptation of the Self-Critical Rumination Scale (SCRS) to the Peruvian context and the validation of its psychometric properties in a sample of university students. As the first step, a linguistic adaptation was made using the back-translation method. After that, to find evidence of validity related to the content, eight judges were sought who gave approval of the translated protocol allowing the development of the Self-Critical Rumination Scale in its Spanish version. A total sample of 220 university students between 19 and 32 years old (M = 22.75, DE = 2.5 completed the adapted version of the SCRS and the Ruminative Responses Scale (RRS). The results refer to a one-dimensional internal structure (81.47% of the common variance) for the scale, obtained from an Exploratory Factor Analysis; internal consistency levels were calculated through the Omega coefficient (¿ = .924); and a positive linear correlation (r = .86, p < 001) with the RRS was found. Based on the collected evidence, it is possible to confirm the correct adaptation of the SCRS in university students from Metropolitan Lima and ensure that the analysis and interpretation of the derived scores of its application are valid in samples of the same characteristics